Profil Hasil Pemeriksaan Dahak Pada Pasien Multidrug-Resistant Tuberculosis (MDR-TB) - Nadza, Alisa Khodrun; Surati, Surati (Jaringan Laboratorium Medis, 2022)
TB patients who do not adhere to OAT treatment can lead to resistance and become MDR-TB and add to the burden of TB management globally. TB control programs including microscopic sputum examination are important for diagnosis, evaluation, follow-up treatment, and follow-up. The results of the sputum examination used the IUATLD scale as an interpretation of the results and the reporting was negative, scanty, positive one, positive two, and positive three according to the number of TB germs found. The results of the sputum examination to determine the classification of the patient, the decision to start treatment, and the patient's recovery. At the step of treatment for MDR-TB patients, the results of sputum examination are an indicator to determine the success rate of treatment which is marked by the conversion of BTA. Research objectives is to determine the description of the results of sputum examination in Multidrug-Resistant Tuberculosis (MDR-TB) patients at the Kendal District Health Center. Research methods is observational research with descriptive research criteria through a cross sectional approach. Respondents of the study were multidrug-resistant tuberculosis (MDR-TB) patients from three health centers in Kendal district with the highest case prevalence. The study respondents were 7 MDR-TB patients. All study respondents, totaling 7 MDR-TB patients (100%), were included in the advanced step of treatment and showed negative sputum examination results. All study respondents (100%) showed that the results of microscopic sputum examination were negative, which means that BTA conversion occurred at the advanced treatment step.